Platelet Activating Factor Receptor Exaggerates Microglia-Mediated Microenvironment by IL10-STAT3 Signaling: A Novel Potential Biomarker and Target for Diagnosis and Treatment of Alzheimer’s Disease - Liu, Junxiu; Jiao, Linchi; Zhong, Xin; Yao, Weifan; Du, Ke; Lu, Senxu; Wu, Yuqiang; Ma, Tianxin; Tong, Junhui; Xu, Mingyue; Jiang, Wenjuan; Wang, Yubao; et al. (Frontiers in Aging Neuroscience, 2022)
Background Early diagnosis and effective intervention are the keys to delaying the progression of Alzheimer’s Disease (AD). Therefore, we aimed to identify new biomarkers for the early diagnosis of AD through bioinformatic analysis and elucidate the possible underlying mechanisms. Methods and Results GSE1297, GSE63063, and GSE110226 datasets from the GEO database were used to screen the highly differentially expressed genes. We identified a potential biomarker, Platelet activating factor receptor (PTAFR), significantly upregulated in the brain tissue, peripheral blood, and cerebrospinal fluid of AD patients. Furthermore, PTAFR levels in the plasma and brain tissues of APP/PS1 mice were significantly elevated. Simultaneously, PTAFR could mediate the inflammatory responses to exaggerate the microenvironment, particularly mediated by the microglia through the IL10-STAT3 pathway. In addition, PTAFR was a putative target of anti-AD compounds, including EGCG, donepezil, curcumin, memantine, and Huperzine A. Conclusion PTAFR was a potential biomarker for early AD diagnosis and treatment which correlated with the microglia-mediated microenvironment. It is an important putative target for the development of a novel strategy for clinical treatment and drug discovery for AD.